A conceptual model for building program sustainability in public health settings: Learning from the implementation of the program sustainability action planning model and training curricula - Moreland-Russell, Sarah; Jost, Eliot; Gannon, Jessica (Frontiers in Health Services, 2023)
Background: The emergence of implementation science has driven an increase in research examining the implementation of evidence-based programs and policies.. However, there has been less attention through program sustainability. To achieve the full benefit of investment in program development and implementation, there must be an understanding of the factors that relate to sustainability; additionally, there is a need for a robust set of tools and trainings to support strategic long-term program sustainability. This paper presents results of our sustainability training intervention and a new conceptual model of sustainability. The proposed conceptual model builds upon the intervention design, further specifying the implementation strategy, strategy-mechanism linkages, and effect modifiers. Methods: This research is part of the larger randomized control trial evaluating the effectiveness of the Program Sustainability Action Planning Model and Training Curricula. Specifically, this multimethod study establishes a conceptual model for program sustainability and related capacity-building interventions. The training intervention was delivered through workshops and technical assistance to 11 state tobacco control programs, principally entailing the development and implementation of a sustainability action plan. We utilize descriptive statistics and participant perspectives to evaluate the training intervention and propose an empirically-grounded conceptual model for sustainability capacity-building interventions in public health settings. Results: Participants found intervention components (workshop, workbook, instructor and resources) to be effective. Overall, participants found the intervention improved their ability to develop sustainability action plans and assess their program and partners. Throughout the study, program managers emphasized the importance of the workshop in providing direction for their sustainability work and the value of robust, ongoing technical assistance. Program managers identified several factors that interfered with intervention reception including staff turnover, competing priorities, partnership challenges, and the COVID-19 pandemic. Conclusion: The present study documents the development and implementation of a novel Program Sustainability Action Planning Model and Training Curricula, one of the first interventions designed to improve program sustainability. In addition, we present an empirically-grounded conceptual model for program sustainability. Considering the paucity of research in this understudied and undefined topic area, this is an important contribution that can serve as a framework for similar intervention designs and implementation efforts.